Contributions of Japanese Hospitalists During the COVID-19 Pandemic and the Need for Infectious Disease Crisis Management Education for Hospitalists: An Online Cross-Sectional Study - Tago M; Hirata R; Katsuki NE; Otsuka Y; Shimizu T; Sasaki Y; Shikino K; Watari T; Takahashi H; Une K; Naito T; Otsuka F; et al. (Dove Medical Press, 2023)
Masaki Tago,1 Risa Hirata,1 Naoko E Katsuki,1 Yuki Otsuka,2 Taro Shimizu,3 Yosuke Sasaki,4 Kiyoshi Shikino,5 Takashi Watari,6 Hiromizu Takahashi,7 Kazunobu Une,8 Toshio Naito,7 Fumio Otsuka,2 Rachel Thompson,9 Susumu Tazuma8,10 1Department of General Medicine, Saga University Hospital, Saga, Japan; 2Department of General Medicine, Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, Okayama, Japan; 3Department of Diagnostic and Generalist Medicine, Dokkyo Medical University, Tochigi, Japan; 4Department of General Medicine and Emergency Care, Toho University School of Medicine, Tokyo, Japan; 5Department of General Medicine, Chiba University Hospital, Chiba, Japan; 6General Medicine Center, Shimane University Hospital, Izumo, Japan; 7Department of General Medicine, Juntendo University Faculty of Medicine, Tokyo, Japan; 8Department of Critical Care and General Medicine, Onomichi General Hospital, Hiroshima, Japan; 9Executive Team, Snoqualmie Valley Hospital, Snoqualmie, WA, USA; 10JR Hiroshima Hospital, Hiroshima, JapanCorrespondence: Masaki Tago, Department of General Medicine, Saga University Hospital, 5-1-1 Nabeshima, Saga, 849-8501, Japan, Tel +81 952 34 3238, Fax +81 952 34 2029, Email tagomas@cc.saga-u.ac.jpIntroduction: Hospitalists in Japan have been at the forefront of the COVID-19 pandemic. However, contributions of Japanese hospitalists during the COVID-19 pandemic and hospitalists' awareness of crisis management education remain unclear.Material and Methods: We conducted a questionnaire survey to investigate the role of Japanese hospitalists during the COVID-19 pandemic. The questionnaire was conducted using email and Google Forms targeting the chairpersons of facilities certified by the Japanese Society of Hospital General Medicine (JSHGM). Members of the academic committee of the JSHGM and several hospitals conducted a narrative review and determined the questions for the survey in a discussion.Results: We conducted descriptive statistics based on the responses of 97 hospitals that agreed to participate in this survey. In total, 91.8% of general medicine departments in the included hospitals were involved in the medical care of COVID-19 patients. Furthermore, in 73.2% of hospitals, hospitalists were involved in infection control for COVID-19 inside or outside the hospital. Our survey revealed that Japanese hospitalists were responsible for COVID-19 treatment in over 60% of hospitals and contributed to hospital management, infection control, and vaccination. In total, 79.4% of hospitals answered that "training of personnel who can provide practical care for emerging infectious diseases is necessary", 78.4% indicated that "the establishment of an infection control system in advance to prepare emerging infectious diseases in the hospital is necessary", and 74.2% stated that "the establishment of an educational system for responding to emerging infectious diseases is necessary.".Conclusion: In conclusion, during the pandemic, in addition to inpatient care, Japanese hospitalists provided outpatient care for COVID-19, which is the role of primary care physicians in other countries. Furthermore, Japanese hospitalists who experienced the COVID-19 pandemic expressed the need for personnel development and education to prepare for future emerging infectious disease pandemics.Keywords: COVID-19 pandemic, hospitalist, hospital management